N- and O-Acetylated 3-Iodothyronamines Have No Metabolic or Thermogenic Effects in Male Mice - Gachkar, Sogol (Eur Thyroid J, 2020)
INTRODUCTION: Injection of 3-iodothyronamine into experimental animals profoundly affects their metabolism and body temperature. As 3-iodothyronamine is rapidly acetylated in vivo after injection, it was hypothesized that the metabolites N- or O-acetyl-3-iodothyronamines could constitute the active hormones. METHODS: Adult male mice were injected once daily with one of the metabolites (5 mg/kg body weight intraperitoneally dissolved in 60% DMSO in PBS) or solvent. Metabolism was monitored by indirect calorimetry, body temperature by infrared thermography, and body composition by nuclear magnetic resonance analysis. Signaling activities in brown fat or liver were assessed by studying target gene transcription by qPCR including uncoupling protein 1 or deiodinase type 1 or 2, and Western blot. RESULTS: The markers of metabolism, body composition, or temperature tested were similar in the mice injected with solvent and those injected with one of the acetylated 3-iodothyronamines. CONCLUSIONS: In our experimental setup, N- and O-acetyl-3-iodothyronamine do not constitute compounds contributing to the metabolic or temperature effects described for 3-iodothyronamine. The acetylation of 3-iodothyronamine observed in vivo may thus rather serve degradation and elimination purposes.